Morpho-Functional Changes in the Skin, Palatal and Buccal Mucosa, and Major Salivary Glands in Iodine Deficiency and Goitrogen Consumption - Valentyna Honcharuk; Iryna Ananevych; Romaniia Barchuk; Oksana Popadynets (Journal of Education, Health and Sport)
Iodine deficiency, combined with daily consumption of natural goitrogens, disrupts thyroid hormone synthesis, resulting in structural and metabolic disturbances within the body. The target organs include the skin, the oral mucosa, and the major salivary glands. Disruptions in these organs provoke changes in multiple systems of the body. However, scientific evidence on the sequential development of morpho-functional changes in these organs under iodine deficiency, in combination with goitrogen consumption, and considering age-related factors, remains limited. Therefore, the purpose of this study was to investigate the morpho-functional changes in the skin, the oral mucosa, and the major salivary glands on the 60th day of iodine deficiency and during goitrogen consumption, considering age-related factors. The experiment was conducted on 50 white non-pedigree male rats, including 25 sexually immature animals (3-5 months old) and 25 sexually mature animals (6-8 months old). Eleven animals from each age group constituted the control group (Group 1). In contrast, 14 animals from each age group were allocated to the experimental groups (Group 2 and Group 3) and exposed to iodine deficiency and goitrogen consumption. Tissue samples were collected on the 60th day of the experiment. Morphological (light microscopy and ultrastructural), morphometric, and biochemical studies were conducted using statistical data processing. In iodine deficiency, accompanied by thyroid status alterations, changes were observed in the epithelium and connective tissue components of the studied organs. Dystrophic-edematous processes progressed in iodine deficiency when combined with the consumption of goitrogens, which exacerbate the hypofunction of the thyroid gland.